2008
DOI: 10.1001/archneur.65.9.1237
|View full text |Cite
|
Sign up to set email alerts
|

Phantosmias and Parkinson Disease

Abstract: Background: Impaired olfaction is a common, nonmotor manifestation of Parkinson disease (PD). However, to our knowledge, qualitative olfactory disturbances, such as odor distortions, have not been extensively reported in this condition. Objective: To describe 2 patients who reported positive olfactory symptoms preceding typical PD, which were consistent with olfactory hallucinations (phantosmias) in the absence of major smell deficit. Design: Case series. Setting: University hospital. Patients: We describe 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
(19 reference statements)
0
48
0
Order By: Relevance
“…A number of case reports could show that some patients have experienced phantosmia very early in the course of the disease [3537]. According to a recent study by Landis et al [38], however, idiopathic phantosmia as an early sign of PD remains probably a rather exceptional presentation whereas the overwhelming majority of people with idiopathic phantosmia will not develop PD.…”
Section: Olfactory Dysfunction As a Prodromal Symptommentioning
confidence: 99%
“…A number of case reports could show that some patients have experienced phantosmia very early in the course of the disease [3537]. According to a recent study by Landis et al [38], however, idiopathic phantosmia as an early sign of PD remains probably a rather exceptional presentation whereas the overwhelming majority of people with idiopathic phantosmia will not develop PD.…”
Section: Olfactory Dysfunction As a Prodromal Symptommentioning
confidence: 99%
“…Recent reports have shown that some patients who developed PD have experienced phantosmia very early in the course of the disease [3,20,21] . However, phantosmia seems to be rather rare in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports identified idiopathic phantosmia to herald diseases such as tumors, chronic rhinosinusitis, intracranial hemorrhages, epilepsy, psychiatric conditions or, as recently suggested, Parkinson's disease (PD) [3] . In idiopathic hyposmia and anosmia, we could recently show that almost 10% of patients develop extrapyramidal symptoms or PD 4 years after initial presentation [4] .…”
Section: Introductionmentioning
confidence: 99%
“…170 Two possible mechanisms have been suggested for phantosmia: either an altered inhibitory input from the primary olfactory neurons, or the presence of peripheral olfactory or trigeminal signals that 'trigger' a central perception. Olfactory perceptual disturbances can also be associated with temporal lobe epilepsy.…”
Section: Human Olfactory Imagerymentioning
confidence: 99%